Norcantharidin enhances antitumor immunity of GM‐CSF prostate cancer cells vaccine by inducing apoptosis of regulatory T cells. Issue 7 (21st June 2018) - Mo, Lijun; Zhang, Xinji; Shi, Xiaojun; Wei, Lili; Zheng, Dianpeng; Li, Hongwei; Gao, Jimin; Li, Jinlong; Hu, Zhiming
Abstract : Norcantharidin (NCTD) is a promising antitumor drug with low toxicity. It was reported to be able to regulate immunity, but the mechanism is not yet clear. Here we explored whether NCTD could enhance the antitumor immunity induced by prostate cancer cell vaccine. The results of the in vitro study showed that NCTD induced apoptosis and inhibited proliferation of regulatory T cells (Tregs). Mechanistic research showed that NCTD inhibited Akt activation and activated FOXO1 transcription, resulting in a pro‐apoptotic effect. The results of the in vivo study showed that more tumor‐infiltrating Tregs existed within peripheral blood and tumor tissue after treatment with the vaccine. Adding NCTD to vaccine treatment could decrease the number of tumor‐infiltrating Tregs and increase the number of CD4 + and CD8 + T cells. Combination therapy with NCTD and vaccine was more effective in inhibiting tumor growth than the vaccine alone. In general, this is the first report that NCTD could induce apoptosis of Tregs and enhance the vaccine‐induced immunity. Abstract : In this paper, we report that NCTD induced apoptosis and inhibited proliferation of Tregs in vitro and its mechanism probably associated with Akt‐FOXO1‐FasL pathway. In addition, there are more Tregs in peripheral blood and infiltrated into the tumor tissues after vaccine therapy and NCTD therapy may overcome the GM‐CSF vaccine‐induced immunosuppressive response and enhance vaccine‐induced effector T cell response in mouse prostate cancer. In general, this is the first report that NCTD could induce the apoptosis of Tregs and promote antitumor immunity of tumor cells vaccine.